In Vitro Dry Matter Digestibility and Organic Matter Digestibility of Fermented Ferns with Mollase and Starbio - Ida Ketut Mudhita; Asih Pujiastuti; Bambang Dedy Harsono (Journal of Tropical Animal Science and Technology, 2022)
This study aims to determine the quality of forage ferns (Gleichenia linearis) as animal feed for ruminants in West Kotawaringin Regency, Central Kalimantan. Ferns fermented with molasses and starbio to determine nutrient content, in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD). This research method uses a completely randomized design (CRD) with four treatments and three replications. The feed treatments were P0 (control): 100% fermented paku resam, P1= P0 + 2% molasses + 2% starbio, P2= P0 + 2% molasses + 4% starbio, and P3 = P0 + 2% molasses + 6% starbio. The parameters of this study were physical quality, feed nutrients, IVDMD and IVOMD. The results showed that the physical quality of all treatments was brown, smelled, and had a hard texture. Nutrients of ferns contain P0= (CP 10.79%, TDN 60.8%), P1= (CP 10.41%, TDN 65.78%), P2= (CP 13%, TDN 68.54%), and P4= (CP 10.90%, TDN 61.14%). The results of IVDMD showed a change (P<0.05) in each fermentation treatment, the highest in P2 of 21.13% or an increase of 40.68% compared to control (15.02%), then in P3 of 18.25% or an increase of 21.5% , and in P1 by 18.2% or an increase of 21.17%. The results of IVOMD showed a change (P<0.05), the highest in P2 of 17.2% or an increase of 12.79% compared to control (15.25%), in P1 of 15.49% or an increase of 1.57%, will but in P3 it was 14.62% decreased by 4.13%. The conclusion of this research is the addition of molasses and starbio to fermented feed increases the digestibility of dry matter and organic matter to the level of molasses 2% + starbio 4%. However, as a ruminant feed ingredient, ferns have a low digestibility.